Pemberdayaan Warga Perumahan Banjararum-Singosari Melalui Rekondisi Fasilitas Penerangan Dan Perbaikan Fasilitas Umum Untuk Meningkatkan Keamanan Lingkungan - Agustriyana, Lisa; Subagiyo, Subagiyo; Witono, Witono; Suwandi, Nicky; Faridha, Nike (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Bumi Banjararum Asri Housing Complex is a housing complex located in Banjararum Village, Malang, East Java. This residence has many features to support the comfort of its residents with a location close to educational institutions, health centers and cyberspace centers around Malang, East Java. Apart from that, the main accommodation in Banjararum Asri is very easy to access by cellphone. However, unfortunately, in the current situation, there are many problems, especially in terms of security and public facilities that need attention, including security against motor vehicle theft and the entry of thieves into people's homes at vulnerable hours, including in public places and conditions roads in residential areas that are damaged. Residents do many things to maintain area security, such as putting up warning flags to warn each other of theft, utilizing Internet of Things (IoT) technology to provide security by residents of RT 15/RW XI. They provide security officers and other security (installing gates and adding lights in several areas), but it is not complete because it requires a relatively large budget. The results obtained from the community empowerment activities of RT 15 Housing Banjararum, Singosari in reconditioning security facilities and road facilities in the RT 15/RW .